Manuscript shapes generated by novel bi-axis control algorithm based on a mathematical handwriting model - Imene Mahmoud; Ines Chihi; Afef Abedlkrim; Mohamed Benrejeb (IAES International Journal of Robotics and Automation (IJRA), 2015)
Handwriting movement is one of the most complex activities of human motions. It’s a blend of kinesthetic, cognitive, perceptual and motor components. The study of this biological process shows that bell-shaped velocity profiles are generally observed in the handwriting motion. In this paper, an identification technique, based on Recursive Least Square algorithm (RLS), is proposed to identify the pen-tip movement in human handwriting process, by using input and output data which present EMG signals and velocities according to x and y coordinates.  Using the estimated coordinates that have resulted from the velocity model; we propose a novel algorithm to generate handwritten graphic traces, which is inspired from the idea of tracing circles by Bresenham bi-axis control algorithm. The effectiveness of this approach should be observed on predicting cursive Arabic letters and Arabic word written on (x,y) plane, these shapes constituting a recorded experimental basis.